Происхождение лит. skanùs ‘вкусный’ в свете структурных и семантических особенностей и-основных прилагательных - Темчин, Сергей Юрьевич (Kalbotyra, 1997)
There is а series of deverbal u-stem adjectives with the meaning ‘tasty, delicious’ in Lithuanian: valgùs : válgyti ‘to eat’; srabùs : srė̃bti ‘to sup, to gulp’; įvadùs : įvèsti ‘to bring in, to take in’; smagùs : smogtis ‘to regale oneself’. It can be assumed that the adjective skanùs ‘delicious, tasty’ has also been derived from a verb. Lith. skinti ‘to pick, to pluck’ meets all the criteria, both formal and semantic. Thus, originally Balt. *skanus must have had the meaning ‘good enough to be picked’, being associated with the names of plants and fruits. Subsequently, semantic development ‘good enough to be picked’ → ‘ripe, juicy’ → ‘tasty, delicious’ took place. It brought this adjective into contrast with Balt. *gardus ‘tasty, delicious’, that had different outcomes in the East Baltic languages. In Lithuanian а complementary dialectal distribution of these two synonyms is to be observed, while in Latvian further semantic development Balt. *skanus ‘tasty, delicious’ → Latv. skāṇš ‘sour(-tаsting)’ has been caused.